EATING OUT SEBAGAI GAYA HIDUP DAN KONSUMERISME DI NANAMIA PIZZERIA DAN IL MONDO YOGYAKARTA - , BUNGA IRFANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research will analyze why young people eat out. This activity becomes a lifestyle for young people in Yogyakarta. Lifestyle is shaped by someoneâs choice about consumerism, his or her social class and it is about creating difference from other social groups. Eating out is a sociospatial activity. Apart from eating, there are other activities which are symbolized through this kind of activity. My case study are 2 pizza shops in Yogyakarta, Nanamia Pizzeria and Il Mondo. These places feature Italianicity, which consist of anything that is related to Italy but not always about the nation. For example the Italian cuisines, interior decoration and atmosphere. This is part of their effort to bring glocalization in these pizza shops then consumed by people. Consumers are not only consuming the food but also images of Italy. Thatâs why eating out is also become a part of glocalization. In the end, eating out reveals how young people create taste, habitus and background. Etnographic research method is used to find how young peopleâs consumption becomes their lifestyle. It is also related to consumerism created in Nanamia Pizzeria and Il Mondo Yogyakarta. In this case, media, especially social media are popular with young people and has an important role as information source and transmission tool.